KARAKTERISTIK DAN DAMPAK MAKROALGA INTRODUKSI - Tri Handayani (Pusat Penelitian Oseanografi LIPI, 2017)
CHARACTERISTIC AND IMPACTS OF INTRODUCED MACROALGAE. An introduced macroalgae is species of macroalgae that have been introduced beyond its native range through human activities and has become successfully established in the new locale. Introduced macroalgae have an impact on ecology and evolution, i.e. direct and indirect competitions with native biota (space monopolization and change in community composition), effects on higher trophic levels (herbivores, associated fauna, toxicity), habitat change (changed structure, sediment accumulation), change of ecosystem processes (alteration of trophic structure) and genetic effects. Introduced macroalgae also have an impact on economy and social, i.e. costs of loss of ecosystem functions or values, impacts on environmental amenity, impacts on human health, management costs (government/non-government), costs of research into introduced species, costs for eradication and control measures and costs for education/extension campaigns. Management of impact and research are needed to minimize the impact of introduced macroalgae.